An unusual case of Cowden syndrome associated with ganglioneuromatous polyposis. Issue 1 (December 2016) - Pistorius, Steffen; Klink, Barbara; Pablik, Jessica; Rump, Andreas; Aust, Daniela; Garzarolli, Marlene; Schröck, Evelin; Schackert, Hans
Abstract Background Ganglioneuromatous polyposis (GP) is a very rare disorder which may be associated with other clinical manifestations and syndromes, such as Cowden syndrome, multiple endocrine neoplasia (MEN) type II and neurofibromatosis (NF) 1. The risk for malignant transformation of ganglioneuromas is unknown, and the combination of GP with colon cancer has been only very seldom reported. Methods and results We report the case of a 60-year old male patient with adenocarcinoma, adenomas and lipomas of the colon and multiple gastroduodenal lesions combined with generalised lipomatosis and macrocephaly. Based on the initial endoscopic and histological findings, a (restorative) proctocolectomy was recommended but declined by the patient. Instead, a colectomy was performed. The histological examination revealed an unforeseen GP in addition to the colon cancer. Extensive molecular diagnostics allowed for the differential diagnosis of the causes of the clinical manifestations, and the clinical suspicion of Cowden syndrome could not be confirmed using Sanger Sequencing and MLPA for the analysis ofPTEN . Finally, a pathogenic germline mutation inPTEN (heterozygous stop mutation in exon 2: NM_000314 (PTEN):c.138C > A; p.Tyr46*) could be detected by next-generation sequencing (NGS), confirming an unusual presentation of Cowden syndrome with GP. Conclusions Cowden syndrome should be considered in cases of GP with extracolonic manifestation and verified by combined clinical and molecular diagnostics. Because GP may represent a premalignant condition, a surgical-oncological prophylactic procedure should be considered. Based on our experience, we recommend early implementation of Panel NGS rather than classical Sanger sequencing for genetic diagnostics, especially if various diagnoses are considered.